Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) Terhadap Hasil Belajar Siswa Kelas X SMAN 1 Sanggar Tahun Pelajaran 2021/2022 - Hairul Imam; Hikmawati; Kosim; Muhammad Taufik (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
The purpose of this study was to determine the effect of the Numbered Heads Together (NHT) cooperative learning model on the learning outcomes of X grade students of SMAN 1 Sanggar. The type of research used is quasi-experimental, with a research design that is pretest-posttest control group design. This research was conducted at SMA Negeri 1 Sanggar from January 2022 to March 2022. The population in this study were all students of class X MIA SMA Negeri 1 Sanggar, Bima Regency, in the 2021/2022 academic year. The sampling technique was carried out by purposive sampling. The samples in this study were students of class X MIA 4 as an experimental class with a Numbered Heads Together (NHT) cooperative learning model and students of class X MIA 3 as a control class with a conventional learning model. The learning outcomes test instrument used was in the form of multiple choices questions as many as 30 questions covering the cognitive domain from C1 to C6. The learning outcomes test instrument before being used in research must also meet the requirements, namely validity, reliability, level of difficulty, and distinguishing power. In this study, two samples of class groups were used so that the homogeneity of variance was tested, normality was tested, and the last was the hypothesis test, namely the t-test. The results showed that there were 20 test instrument questions that met the requirements. The average value in the experimental class is 79.00, while in the control class is 69.35. From the data analysis based on the F test, the research data was homogeneous, and based on the x2 test, it was found that the data were normally distributed. Based on the t-test, it was found that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. The conclusion is that there is an effect of the Numbered Heads Together type of cooperative learning model on the improvement of physics learning outcomes for class X SMA Negeri 1 Sanggar in the 2021/2022 academic year.